Silicon Alleviate Hypoxia Stress by Improving Enzymatic and Non-enzymatic Antioxidants and Regulating Nutrient Uptake in Muscadine Grape (Muscadinia rotundifolia Michx.) - Iqbal, Zafar; Sarkhosh, Ali; Balal, Rashad Mukhtar; Gómez, Celina; Zubair, Muhammad; Ilyas, Noshin; Khan, Naeem; Shahid, Muhammad Adnan (Frontiers in Plant Science, 2021)
Flooding induces low oxygen (hypoxia) stress to plants and this scenario is mounting due to hurricanes followed by heavy rains, especially in subtropical regions. Hypoxia stress results in the reduction of green pigments, gas exchange (stomatal conductance and internal CO2 concentration) and photosynthetic activity in the plant leaves. In addition, hypoxia stress causes oxidative damage by accelerating lipid peroxidation due to the hyperproduction of reactive oxygen species (ROS) in leaf and root tissues. Furthermore, osmolyte accumulation and antioxidant activity increase, while micronutrient uptake decreases under hypoxia stress. Plant physiology and development get severely compromised by hypoxia stress. This investigation was, therefore, aimed at appraising the effects of regular silicon (Si) and silicon nanoparticles (SiNPs) to mitigate hypoxia-stress in muscadine (Muscadinia rotundifolia Michx.)grape plants. Our results demonstrated that hypoxia stress reduced muscadine plants’ growth by limiting the production of root and shoot dry biomass. Whereas the root zone application of both Si and SiNP effectively mitigated oxidative and osmotic cell damage. Compared to Si, SiNP yielded better efficiency by improving the activity of enzymatic antioxidants (including superoxide dismutase, peroxidase, and catalase), non-enzymatic antioxidants (ascorbic acid and glutathione contents), and accumulation of organic osmolytes (proline and glycinebetaine). SiNP also regulated the nutrient profile of the plants by increasing N, P, K, and Zn contents while limiting Mn and Fe concentration to a less toxic level. A negative correlation between antioxidant activities and lipid peroxidation rates was observed in SiNP-treated plants under hypoxia stress. Conclusively, SiNP-treated plants more efficiently combat hypoxia more efficiently stress than conventional Si by boosting antioxidant activities, osmoprotectant accumulation and micronutrient regulation.